Faktor yang Mempengaruhi Partisipasi pria pada Penggunaan Alat Kontraspesi: Penelitian Observasional - Murti, Ni Nyoman; Rahmawati, Eli; Pasiriani, Novi (Health Information : Jurnal Penelitian, 2023)
The population growth rate in Indonesia is still high and the Family Planning program continues to be promoted. As an effort to strengthen participation in the Family Planning program, it is necessary to involve men in promotion and education. This study aims to examine factors related to men's participation in using contraception. The study was conducted in Gunung Mulia Village with a total of 54 male respondents selected using purposive sampling technique from a population of 425 fertile couples. Data collection was done using a questionnaire instrument. Data analysis was performed using frequency distribution and statistical analysis with the Chi-square test. The results showed a statistical correlation between the variables of knowledge (p=0.000), education (p=0.000), patriarchal culture (p=0.000), and access to health services (p=0.000). There is a relationship between men's participation in using contraception and knowledge, education, patriarchal culture, and access to health services. Further research is needed by adding other factors that may be related to the use of contraception.